2008
DOI: 10.1016/j.imlet.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

CD5 plays an inhibitory role in the suppressive function of murine CD4+ CD25+ Treg cells

Abstract: A subset of CD4 + T cells, the CD4 + CD25 + T reg cells in the lymphoid organs and peripheral blood are known to possess suppressive function. Previous in vitro and in vivo studies have indicated that T cell receptor (TCR) signal is required for development of such 'natural regulatory (T reg ) cells' and for activation of the effector function of CD4 + CD25 + regulatory T cells. CD5 is a cell surface molecule present on all T cells and a subtype of B lymphocytes, the B-1 cells, primarily localized to coelomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 67 publications
6
34
2
Order By: Relevance
“…This hyperproliferation was already reported [74] and argues in favor of a role of CD5 as a negative regulator of TCR signaling in mature T cells. Our results showed efficient suppressive activity of CD5 À/À Treg; however, a more detailed study recently showed that Treg obtained from CD5 À/À mice are even more potent than WT Treg in suppressing the in vitro cell proliferation of anti-CD3 stimulated CD4 1 CD25 À responder T cells [75].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This hyperproliferation was already reported [74] and argues in favor of a role of CD5 as a negative regulator of TCR signaling in mature T cells. Our results showed efficient suppressive activity of CD5 À/À Treg; however, a more detailed study recently showed that Treg obtained from CD5 À/À mice are even more potent than WT Treg in suppressing the in vitro cell proliferation of anti-CD3 stimulated CD4 1 CD25 À responder T cells [75].…”
Section: Discussioncontrasting
confidence: 58%
“…This hyperproliferation was already reported [74] and argues in favor of a role of CD5 as a negative regulator of TCR signaling in mature T cells. Our results showed efficient suppressive activity of CD5 À/À Treg; however, a more detailed study recently showed that Treg obtained from CD5 À/À mice are even more potent than WT Treg in suppressing the in vitro cell proliferation of anti-CD3 stimulated CD4 1 CD25 À responder T cells [75].In conclusion, our data demonstrate that the enrichment of nTreg observed in the absence of CD5 signaling, under conditions of enhanced TCR-mediated signaling is due both to increased nTreg selection and to preferential cell death of naïve thymocytes, while nTreg appear to be less sensitive to conditions of high avidity. The reduced Akt phosphorylation observed CD4 1 CD25 À naïve CD5 À/À thymocytes in response to TCR crosslinking might explain the increased cell death of these cells, suggesting a new potential mechanism for CD5-mediated thymocyte survival.…”
contrasting
confidence: 55%
“…Sakaguchi et al demonstrated that depletion of the CD5 high T cell population also depleted majority of CD4 + CD25 + T cells simultaneously [27]. Recently, the inhibitory role of CD5 has been reported in the murine T reg cell suppressive function [28]. In our data, CD5 expression was significantly correlated with Foxp3 expression in HTLV-1-infected cells (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…33). The amount of CD5 displayed on the cell surface is proportional to the intensity of signals received through the TCR, and CD5 is robustly expressed on Treg cells (34,35). To test whether CD5 more specifically inhibits signaling in Treg cells, we analyzed Erk phosphorylation after CD3/CD28 cross-linking across five matched ranges of surface CD5 (Fig.…”
Section: Significancementioning
confidence: 99%